Yabancılık Unsuru Taşıyan Bireysel İş Sözleşmelerinden Kaynaklanan Uyuşmazlıklarda Türk Mahkemelerinin Yetkisi: MÖHUK m.44 - (:unkn) unknown (My University, 2019)
MÖHUK m.44 bireysel iş sözleşmelerinden kaynaklanan uyuşmazlıklarda Türk mahke-melerinin yetkisini özel olarak düzenlemiştir. Bu maddeye göre işçi aleyhine açılan davalarda mutat işyeri mahkemesi; buna karşılık işveren aleyhine açılan davalarda işverenin yerleşim yeri, işçinin yerleşim yeri veya mutat meskeni mahkemesi de yetkilidir. Maddenin konuluş amacı zayıf taraf konumunda olan işçinin korunmasını sağlamaktır.Ancak mutat işyerinin yurt dışında olduğu uyuşmazlıklarda MÖHUK m.44 işçi aleyhi-ne açılacak davalarda Türkiye’de yetkili bir mahkeme tesis etmemektedir. Bu husus açıkça maddenin konuluş amacına aykırılık teşkil etmektedir. Bu durumda MÖHUK m.40 uyarınca iç hukukun yetki kurallarına başvuru mümkün müdür? Diğer taraftan MÖHUK m.44 kuralı münhasır yetki olarak yorumlanırsa, bunun sonucu yabancı mahkemeden verilen kararların ta-nınması ve tenfizinin MÖHUK m.54/b’ye göre mümkün olmamasıdır. Bu makalede özellikle mutat işyerinin Türkiye dışında olduğu durumlarda Türk mahkemelerinin yetkisi; MÖHUK m.44 kuralının münhasır yetki tesis edip etmediği ve son olarak yabancı mahkeme kararlarının MÖHUK m.54/b’ye göre tenfiz engeline takılıp takılmadığı irdelenmiştir.

Art 44 of MÖHUK provides a special jurisdiction rules regarding the conflicts arising out of the individual employment contracts. Under this Article, an employee will be sued in the court for the place where the employee habitually carries out his work while an employer will also be sued the court of the place where the employer is domiciled, the employee is domiciled or the employee has habitual residence. The main purpose of this Article is to protect the employee who is a weak party. However, if the place where the employee habitually carries out his work abroad, Art 44 of MÖHUK does not provide a jurisdiction for Turkish courts for the case filed against the employee. This is expressly conflict with the main purpose of Article. In this regard, is it possible to apply domestic jurisdiction rules based on Art 40 of MÖHUK? On the other hand, if Art 44 is understood that Turkish courts’ jurisdiction is exclusive for disputes arising out of individual employment contracts, consequently, foreign court decisions will not recognized or enforced in Turkey under Art 54/b of MÖHUK. Here, the article reviews the jurisdiction issues of Turkish courts especially when the work place is out of Turkey and whether the jurisdiction of Turkish courts based on Art 44 of MÖHUK will be exclusive or not and finally whether foreign judgments will be denied to be enforced because of Art 54/b of MÖHUK.
The Jurisdiction of Turkish Courts in the Conflicts Arising Out of the International Individual Employment Contracts
Keywords: Hukuk